Heterogeneous DNA methylation and gene expression patterns underly metabolic plasticity in canine astrocytoma-derived stem-like cells - Toedebusch, Ryan G.; Hwang, Chang-il; Syed-Quadri, Shafee; Aboud, Orwa; Woolard, Kevin D.; York, Daniel; Parys, Maciej; Dickinson, Peter J.; Meyers, Frederick J.; McPherson, John D.; Toedebusch, Christine M. (Frontiers in Oncology, 2026)
IntroductionGlioma stem cells (GSCs) have been implicated in radio- and chemotherapeutic resistance of glioblastoma (GBM). Therapeutic targeting of GSCs has shown promise in immunocompromised rodent models but have not been translated into effective therapies for human patients. These failures underscore the translational limitations of rodent models and highlight the need for complementary models that accurately and reliably predict therapeutic translation for human HGG. Spontaneous canine high-grade gliomas (HGGs) may provide a complementary translational model for human therapeutic development. While described in canine HGGs, little is known about canine glioma stem cell biology.MethodsHere, we evaluated cellular metabolism, cytosine modifications, gene expression, and functional tests of malignancy to interrogate differences between canine high-grade astrocytoma-derived glioma stem-cell like cells (GSLC) and a traditional non-stem cell glioma cell line following exposure to hypoxia. ResultsHypoxia increased oxygen consumption rates in GSLCs and augmented features of malignancy in GSLCs. We observed variable cytosine modifications and mRNA expression across cell lines, and our data did not correlate cytosine modification patterns with oxygen consumption capacity following hypoxia. However, we did demonstrate a positive correlation between up-regulated genes in human GBM GSCs and hypomethylation of orthologous canine genes following hypoxia.DiscussionTogether, these data support that hypoxia enhances distinct stem-like traits in canine astrocytoma GSLCs, similar to human GSCs.